Three-dimensional self-similar super-repellent films for underwater display and wettability switching. Issue 43 (22nd October 2019) - Liu, Maolin; Luo, Yuanfang; Jia, Demin
Abstract : A robust, self-similar super-repellent film with pattern manipulation and erasion healing features for underwater display and wettability switching has been fabricated. Abstract : Given the intrinsic sensitivity toward harsh settings and the new requirements in emerging fields, the development of bio-inspired materials, particularly super-repellent materials, has been severely restricted in many practical scenarios. In this work, a robust self-similar super-repellent film (SSF) with pattern manipulation and erasion healing for underwater display and wettability switching was successfully fabricated via a facile bulk-deposition method. The strategic integration of covalently cross-linked networks with hierarchical topography through solidification and dehydroxylation commendably conferred extreme super-hydrophobicity on SSF. Due to the three-dimensional super-hydrophobicity and regenerative characteristics, the SSF repeatedly realized wettability switching (>5 times) between super-hydrophobic and super-hydrophilic states by means of the erasion healing approach. More importantly, the novel combination of pattern manipulation and light-reflective phenomena enabled SSF to successfully achieve underwater display with the employment of flash-light. Furthermore, the embedded bio-inspired wettability on SSF remained unaltered after being subjected to various severe physical settings (>60 times), highly corrosive phases (pH 1–14), boiling/ice water, and outdoor experiments. Our findings convincingly stand out as a new tool for advancing the synthesis of robust and versatile super-repellent materials for various promising applications.